2018
DOI: 10.1002/pbc.27038
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury after high dose etoposide phosphate: A retrospective study in children receiving an allogeneic hematopoetic stem cell transplantation

Abstract: This study shows that EP at high dosage or one of its excipients is probably responsible for AKI, as compared to CY. Further studies are required to explore the origin of this adverse effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Etoposide and TOP2 poisons are highly efficacious chemotherapy agents. Yet, differences in resistance across tumors and the toxicity associated with such treatments undermines the risk/benefit ratio that this therapy can offer to individual patients 36, 37, 38, 39, 40, 41 . To overcome this, biomarkers for etoposide and doxorubicin response are necessary, but virtually non-existent.…”
Section: Discussionmentioning
confidence: 99%
“…Etoposide and TOP2 poisons are highly efficacious chemotherapy agents. Yet, differences in resistance across tumors and the toxicity associated with such treatments undermines the risk/benefit ratio that this therapy can offer to individual patients 36, 37, 38, 39, 40, 41 . To overcome this, biomarkers for etoposide and doxorubicin response are necessary, but virtually non-existent.…”
Section: Discussionmentioning
confidence: 99%
“…Etoposide phosphate is preferred to etoposide because the latter poses a high risk of precipitation when highly concentrated . Two recent reports have highlighted the risk of acute kidney injury (AKI) due to etoposide phosphate . The Odds ratio to develop AKI linked to the use of EP at 60 mg/kg compared to cyclophosphamide at 60 mg/kg over 2 days combined with TBI was computed at 6.0 with a loss of renal function ranging between −44.5 and −71% .…”
Section: Diagram Of the Strengths Weaknesses Opportunities And Thrmentioning
confidence: 99%
“…Two recent reports have highlighted the risk of acute kidney injury (AKI) due to etoposide phosphate . The Odds ratio to develop AKI linked to the use of EP at 60 mg/kg compared to cyclophosphamide at 60 mg/kg over 2 days combined with TBI was computed at 6.0 with a loss of renal function ranging between −44.5 and −71% . The presence of an excipient in the formulation of Etopophos ® , Dextran 40 (300 mg/vial), leads us to strongly suspect this drug of being involved in the observed phenomenon .…”
Section: Diagram Of the Strengths Weaknesses Opportunities And Thrmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of at-risk excipients has notably been studied in pediatric intensive care units. 4 A recent study found that etoposide phosphate (used in hematopoietic stem-cell transplantation) may induce acute kidney injury, 5 because of the presence of the excipient dextran 40. However, the replacement of etoposide phosphate by standard etoposide would expose children to an even higher dose of ethanol (30 g, on average).…”
Section: Introductionmentioning
confidence: 99%